Characteristics of COVID-19 Therapy Based on Disease Severity at Siloam Kebon Jeruk Hospital - Tjahyanto, Teddy; Herwanto, Velma (Medicinus, 2024)
Introduction : COVID-19 is an infectious disease that can cause acute respiratory syndrome by droplet transmission. Along with the very fast spread of the virus which occurs in almost all countries, it is necessary to have therapies that can reduce the morbidity and mortality of patients infected with COVID-19. Various factors affect the administration of therapy so a management guideline is needed for medical personnel so that the administration of therapy can be consistent and efficient in accordance with scientific evidence. This study aims to determine the characteristics and therapeutic options of COVID-19 patients based on the severity of the disease so it can be an evaluation for policymakers and health workers in providing COVID-19 therapy. Methods : This type of research is descriptive, and the research design is cross-sectional with a total population sampling. The study was conducted at Siloam Kebon Jeruk Hospital with a total of 135 respondents from secondary medical record data. Results : The observed data include the characteristics of the respondents and the therapies for COVID-19 patients, which consist of antiviral, anti-inflammatory, and anticoagulant treatments. Based on the collected data, COVID-19 patients were predominantly male (55.6%) with an average age of 55 years. Many patients presented with moderate severity without requiring oxygen (34.1%) and were classified as having referred outcomes (47.4%). Antiviral therapy using favipiravir was predominantly administered to patients with mild to moderate severity, while remdesivir was mostly given to those with moderate to severe severity. Corticosteroids, such as dexamethasone and methylprednisolone, were the preferred choice for anti-inflammatory therapy (72.2%). Heparin was the most commonly used anticoagulant therapy across all severity levels, and antibiotics were administered to the majority of patients infected with COVID-19 (73.3%). Conclusions : Evaluation of the low rate of use of corticosteroids and anticoagulants in COVID-19 patients is needed.